Inclusive Education with Serious Games and User-Centered Design, exploring the intersection of accessibility and usability - Claudia Screpnik; Francisca Negre-Bennasar; Jesús Salinas (Revista Latinoamericana de Tecnología Educativa)
The advancement of technology enables new resources for education. The convergence of accessibility, usability, serious games (SG), and user-centered design (UCD) enables the development of inclusive resources to meet the needs of people with disabilities. This work aims to analyze and synthesize the developments of digital educational games, focusing on technical aspects to facilitate their implementation in the classroom. The criteria and recommendations of the PRISMA protocol (2020) were applied to conduct the search. Keywords were used to explore the Web of Science, Scopus, PubMed databases, and 21 journals, covering the period from 2018 to 2023. Initially, 799 articles were identified, and after the refinement process, 24 publications were analyzed. The results indicate a growing and ongoing interest in the topic. Current trends in the design and use of accessible video games for individuals with intellectual disabilities were identified, along with their impact on learning and educational inclusion.